Experimental investigation on hysteric loading characteristics of fly ash as fractional substitute of cement in reinforced concrete beam‐column connection at curing of 90 days. (11th August 2021) - Shaw, Sayan Kumar; Ghosh, Satyaki; Dey, Abhijeet; Sil, Arjun
Abstract: Fly ash becomes a fine gray particles consisting generally of globular, smooth particles available in coal ‐fired power stations. In this work, the seismic performance of beam‐column connection (BCC) has been examined by applying fly ash as a surrogate of cement. Five different samples of BCC's, with or without admixtures were casted as well as examined in order to obtain the hysteric loading characteristics for a curing period of 90 days. The tested samples designed for M25 grade of concrete having water–binder ratio maintaining as 0.4. From the study, it has been found that BCC sample having 20% fly ash along with super plasticizer subjected to 90 days curing (i.e., BCC sample of 20FAS90) exhibits a better performance as compared to the other tested samples. The BCC sample of 20FAS90 showed higher displacement as compared to controlled concrete without fly ash and super plasticizer at 90 days (Control90). Also, from the experimental work, it has been found that 20FAS90 sample possesses 18% higher ductility as well as 70% higher energy dissipation than the Control90 sample. Additionally, regarding brittleness index (BI) of 20FAS90 sample exhibits 25% lower as compared to Control90 sample. Furthermore, the stiffness degradation of the sample becomes slightly higher than the controlled concrete. Therefore, the paper essentially highlights the importance of fly ash and super plasticizer on the dynamic performance of the BCC samples at 90 days curing period such that an advanced mix design criterion could be put forward for optimum replacement of cement leading to higher safety aspects.